Mitigation potential for increasing soil organic carbon of rice fields in Bangladesh – a case study - Walton, Jack; Kuhnert, Matthias; Begum, Khadiza; Kader, Mohammed Abdul; Dondini, Marta; Hillier, Jon; Wollenberg, Eva Karoline; Smith, Pete (Copernicus GmbH, 2020)
In order to limit global warming to 2°C, a variety of mitigation measures are needed, including those that result in net negative emissions. Soil carbon sequestration (SCS) through changed land management practices has the potential to help meet this need, but it requires further study to represent a viable policy option. Rice cultivation plays a major role in South Asian agriculture, accounting for almost 40% of the crop’s harvested area worldwide. Its greenhouse gas (GHG) profile means it contributes disproportionately more than other crops to the region’s emissions. Adapting rice system management for SCS may therefore represent a compelling mitigation opportunity for the agricultural sectors of South Asian countries. This study uses a process-based modelling approach to compare the performance of two models, ECOSSE and DAYCENT, in assessing the mitigation potential of increasing soil organic carbon (SOC) stocks on a Bangladeshi test site under rice cultivation. A previous study using DAYCENT showed an increase in SOC stock as well as an overall GHG emissions reduction for several management practices relative to the baseline scenario. ECOSSE, calibrated to the same measurements, also showed an increase in SOC and net emissions reduction relative to the baseline. However, the models differed significantly in the extent of mitigation predicted as well as the GHG emissions profile. Given these differences, further analysis is needed to reduce error and uncertainty in these models. The results of this study form a basis for spatial model approaches to assess the mitigation potential of rice production in Bangladesh.